+0  
 
0
84
1
avatar

–12(x + 6.2) = 60

Guest Apr 24, 2017
Sort: 

1+0 Answers

 #1
avatar+4164 
+2

-12(x + 6.2) = 60

 

Divide both sides of the equation by -12 .

x + 6.2 = 60/-12

 

x + 6.2 = -5

 

Subtract 6.2 from both sides of the equation.

x = -5 - 6.2

 

x = -11.2

hectictar  Apr 24, 2017

11 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details